Biological wastewater treatment: Comparison of heterotrophs (BFT) with autotrophs (ABFT) in aquaculture systems. (January 2020) - Kim, Kyochan; Hur, Jun Wook; Kim, Soohwan; Jung, Joo-Young; Han, Hyon-Sob
Highlights: The wastewater treatment capacity of heterotrophs is superior to that of autotrophs. The BFT system requires more energy for aquaculture than does the ABFT system. Both systems showed excellent water-purification capacities compared to the control. The BFT and ABFT systems could be economical aquaculture systems. Abstract: The present study was conducted to compare wastewater purification capacities between heterotrophs (BFT) and autotrophs (ABFT) and to evaluate the effects on the growth of fish (Nile tilapia, Oreochromis niloticus ) in aquaculture systems. The wastewater treatment capacity of heterotrophs is far superior to that of autotrophs, but the BFT system requires more energy for aquaculture than does the ABFT system. Regardless, both systems effected positive influences on fish growth performance, showing excellent water-purification capacities compared with the control group (CON). No significant differences were found between CON and ABFT or between ABFT and BFT, but there were significant differences between CON and BFT. Both systems BFT and ABFT were revealed to be cost effective in relation to CON, having reduced water replacement by 82%. Therefore, the BFT and ABFT systems could be economical aquaculture systems if due advantage is taken of what both have to offer.